O processo de aprendizagem organizacional em central cooperativa agroindustrial : o caso FRIMESA - Royer, Douglas (2010)
The learning processes are present at all organizational levels, from the macro-organizational levels to the collective and individual instances, assuming the position of the pillars of strategic management. Therefore, the ability of the organization be structured as a learning system works with the construction of a more dynamic and relevant to the existing competitive landscape. This dissertation it is a study on organizational learning in the environment of agribusiness, where the construction of knowledge and technological innovation have sought to shape the conduct and operation of productive processes in the countryside and, through industrialization, the middle urban. Having a central cooperative agribusiness as a unit of study, the study turned out to be a social research, with qualitative approach, with an exploratory-descriptive of its object of study "Organizational Learning - AO". After a review of major theoretical concepts of organizational learning on the model adopted and the characteristics of cooperative organizations in the agribusiness, for empirical research, we opted for "Case Study" as a research strategy for understanding organizational learning in FRIMESA , a central cooperative agribusiness. The empirical research coupled with the theoretical framework used allowed the analysis of the process of organizational learning in FRIMESA the perspective of the organization and in light of the model OADI-SMM, and the cooperative as an individual and identifying the possible factors of embarrassment in the process of AO.